An Academic Self-Efficacy as a Predicator of Senior High School Students’ Participation in English Debate Club - Anggun Mukti Prima Bakti; Diah Kristina; Sumardi Sumardi (STAI Hubbulwathan Duri, 2022)
Self-efficacy (SE) is defined as public belief in their capacity to attain intended goals via their actions. Within an academic setting, SE is frequently referred to as Academic Self-Efficacy (ASE), which impacts learner judgments about one's ability to effectively achieve educational goals. To succeed in an academic context, students must complete several academic tasks in a variety of subjects. Fear of public speaking is one of the most major challenges that students face. In an EFL context, where learners have few opportunities to practice public speaking in real-life circumstances, debate helps them to use the language to communicate their viewpoints coherently. This study is important to identify students' levels of academic self-efficacy and how they function as a predictor of academic achievement. The qualitative case study is used to explore the problem in-depth in natural setting. The data were collected from open-questionnaire and semi structured interview. The participants of the study were included nine senior high school students who are the members of Debate Club. According to the findings of this study, Academic self-efficacy influences students' motivation to join the debate club. Prior debate club experience of members became the most essential consideration for students who joined the debate club. Vicarious experience is the second most crucial aspect in students' decision to join the debate club. Then there's social persuasion, which is crucial since it serves as a role model for students. Seniors or peers who have accomplished a lot may use their success to encourage other students to join them. Another outcome is that members have strong emotional well-being, so even if they fail or have difficulties participating, they do not abandon all debate club activities. Another study was planned to involve more debate club members and to examine the teacher's role as debate supervisor.